Objectively Measured Changes in Physical Activity and Sedentary Behavior in Cardiac Rehabilitation: A PROSPECTIVE COHORT STUDY. Issue 6 (November 2018) - Freene, Nicole; McManus, Margaret; Mair, Tarryn; Tan, Ren; Davey, Rachel
Abstract : Purpose: Physical inactivity and sedentary behavior (SB) are independent risk factors for cardiovascular disease and all-cause mortality. No studies appear to have investigated whether SB in cardiac rehabilitation (CR) participants changes over time. The aim of this study was to objectively assess physical activity (PA) and SB of CR participants over 6 wks. Methods: Using a prospective cohort study design, 72 CR participants, age = 64.2 ± 9.6 y (mean ± standard deviation [SD]) (79% male), wore an ActiGraph ActiSleep accelerometer for 7 consecutive days at the beginning and end of a 6-wk program to assess daily minutes of moderate-to-vigorous PA (MVPA) and SB (<100 counts/min). Other outcomes collected were self-reported MVPA (Active Australia Survey) and SB (Past-Day Adults' Sedentary Time Questionnaire), body mass index, waist-to-hip ratio, lipid profile, blood glucose level, quality of life (MacNew), exercise capacity (6-min walk test), anxiety and depression (Hospital Anxiety and Depression Scale). Results: Time spent in MVPA and SB did not change over 6 wks. However, exercise capacity and light-intensity PA significantly improved ( P < .01). On average, participants spent 11.8 ± 1.1 hr daily in SB, with 9.5 ± 14.7 min daily in MVPA at the end of the CR program. There was some evidence that males and females had different movement patterns. Conclusions: Levels of PA are low and SB is high in CR participants despite changes in exercise capacity over 6 wks. Participants in CR did increase their PA but only in the light-intensity range. Alternative approaches in CR should be considered to encourage participants to move more and sit less. Abstract : Physical inactivity (PA) and sedentary behavior (SB) are independent risk factors for cardiovascular disease. There are few studies investigating PA and SB in cardiac rehabilitation (CR). This study found CR participants did not change their daily moderate-intensity PA and SB from the beginning to end of a 6-wk CR program.